Constructing small talk in learner-native speaker voice-based telecollaboration: A focus on topic management and backchanneling - Barron, Anne; Black, Emily (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
Developments in technology, including the use of synchronous telecollaborative tools, promise to address the challenge of providing opportunities for interaction in the foreign language classroom. The present study investigates how learners and native speakers (NS) of English co-construct small talk in the opening phase of a voice-based Skype telecollaboration. Specifically, learner and NS self-oriented and other-oriented topic shifts, topic replies and verbal listenership behaviour are analysed. The focus is on the English interactions of two learner-NS dyads, each made up of a German NS and an Irish English NS. One dyad includes a learner who exhibits a high level of interactional competence while in the other dyad the learner shows no active participation. Specifically, she reveals a low use of topic shifts, a high use of equivocal short-form topic replies, few long-form replies and a very limited use of backchannels/backchannel forms, leaving the interactional burden on the Irish English NS. The analysis illuminates small talk construction in the voice-based telecollaborative context and highlights the possibilities it offers for developing interactive competencies. It also sheds light on the roles played by NS and learners in topic management and adds to our understanding of individual differences in small talk construction in the foreign language.
Keywords: Telecollaboration; Backchannel; Topic Selection; Topic Development; Small Talk; Computer Mediated Communication; Interactional Competence; Pragmatic Competence; 420 Englisch, Altenglisch